How do We Empower Youth to be Catalysts of Change: An Exploration of Pedagogies utilised in Non-formal Peace Education in Sri Lanka (A Case Study of a Non-Governmental Organisation) - Jayatilake Kankanamalage, Janith Prabashwara Perera (2022)
The contribution of youth is vital for attaining Positive Peace. Peace Education as an important post-conflict peacebuilding strategy enhances knowledge, skills, values, and attitudes of youth capacitating them to make meaningful social impact. Non-Governmental Organisations (NGOs) conduct Non-formal Peace Education programmes targeting youth overcoming the limitations of the formal system. To ensure that Peace Education is delivered effectively to youth, NGOs must consider whether pedagogies utilised cater into the interests and needs of the learners. This empirical research tries to identify pedagogical practices that are youth-centric and empowering youth to be change agents of peace in the context of Post-Conflict Sri Lanka.